Dari Monolog Tafsir ke Praxis Makna: Hermeneutika Eksistensial sebagai Kritik atas Krisis Keberpihakan dalam Studi Teks Keagamaan - Amira Elisia Putri; Nafisah Arzalia; Kharisma Hanum Inzani; Ali Hasan Siswanto (Indo Publishing, 2026)
This article departs from the epistemological and existential crisis in the study of religious texts, characterized by the dominance of interpretive monologues, the freezing of meaning, and the absence of ethical alignment with social reality. In this context, texts are often reduced to normative instruments detached from the dynamics of modern human suffering, thus failing to function as a living source of meaning. The research gap lies in the minimal integration between textual hermeneutics, the theology of alignments, and existential psychology approaches, which have developed separately without adequate conceptual synthesis. This article aims to reconstruct textual dialogue through an existential hermeneutic framework by integrating the theology of alignments with Viktor Frankl's thoughts on the will to meaning and the crisis of meaning (existential vacuum). This research uses a qualitative-philosophical approach based on literature review with hermeneutic-critical and interdisciplinary analysis. The article's main argument is that textual dialogue must be repositioned from a normative interpretative practice to an existential and alignmental praxis of meaning, by positioning the interpreter as an ethically responsible subject seeking meaning. Thus, the text is not only understood as a source of law, but as a liberating space for the transformation of meaning. This article's scholarly contribution is the formulation of an